Metastatic melanoma to the orbit masquerading as idiopathic orbital inflammation: a case report - Fernandes, Joshua J.; Sharabura, Anna B.; Pfannenstiel, Matt M.; Sokol, Jason A. (Frontiers in Ophthalmology, 2025)
PurposeThis case highlights an exceedingly rare presentation of secondary orbital melanoma and reviews the current literature on orbital melanoma.Case presentation: A 39-year-old man was referred to our clinic after acute-onset decreased vision and left upper eyelid ptosis. Outside-hospital magnetic resonance imaging (MRI) showed an enhancing left superior orbital apex mass. The patient was initially treated for presumed idiopathic orbital inflammation without improvement. An orbital biopsy was performed, and the pathology showed secondary malignant melanoma. A computed tomography (CT) chest scan showed likely pulmonary metastases. Upon further questioning, the patient reported a history of an incompletely excised pigmented forearm lesion. The patient was treated systemically with nivolumab and ipilimumab.Conclusions and importance: Despite its rarity, orbital melanoma should be considered in the differential diagnosis of patients with an orbital apex mass that does not respond to treatment for idiopathic orbital inflammation.